Analisis Kinerja Keuangan pada Koperasi Simpan Pinjam Kopdit Obor Mas di Kota Kupang - Dian Bale Toda; Markus U.K. Yewang; Andri P. Loe (Student Research Journal, 2026)
This study aims to analyze the financial performance of the Obor Mas Kupang Savings and Loan Cooperative using financial ratio analysis, including liquidity, solvency, profitability, and activity ratios during the 2022–2024 period. The research method used is descriptive quantitative, with financial ratio analysis consisting of the Current Ratio (CR), Debt to Asset Ratio  (DAR), Debt to Equity Ratio  (DER), Return on Asset s (ROA), Return on Equity  (ROE), and Total Asset Turnover. The data used are the cooperative’s financial statements, including the balance sheet and the Statement of Remaining Operating Results (SHU). The results show that from a liquidity perspective, the Current Ratio decreased from a very unhealthy category in 2022 and 2023 to a fairly healthy category in 2024, indicating an improvement in managing short-term liabilities. From a solvency perspective, the Debt to Asset Ratio  remained in the very unhealthy category throughout the study period, as total liabilities exceeded total assets, while the Debt to Equity Ratio  showed improvement from less healthy to fairly healthy. From a profitability perspective, both Return on Asset s and Return on Equity  indicate low and unstable performance, falling into unhealthy to very unhealthy categories. From an activity perspective, Total Asset Turnover shows fluctuating performance, experiencing a decline and then improvement, but remaining unstable.